Nutrition Strategies for Optimizing Performance and Health in Young Athletes - Kinga Woźniak; Patryk Hedesz; Aleksandra Żuk-Łapan; Magdalena Jung; Monika Gardian-Baj; Justyna Popczyńska; Aleksandra Doryń; Maximilian Jung; Emilia Babula; Aleksandra Włodarczyk; Andrzej Taras (Kazimierz Wielki University, 2024)
Introduction: The increasing participation of young individuals in sports necessitates a comprehensive understanding of the intricate relationship between nutrition and athletic performance during the critical adolescent years. This introduction sets the stage for an exploration of the dynamic nutritional needs of young athletes, emphasizing the pivotal role of nutrition in supporting growth, energy metabolism, and overall athletic achievement. Current State of Knowledge: The current state of knowledge encompasses an in-depth analysis of key nutritional considerations for young athletes. Examining energy and macronutrient requirements, micronutrient considerations, hydration strategies, and optimal timing of nutrition, this section synthesizes existing research to provide evidence-based guidelines. Furthermore, it addresses the unique challenges posed by different sports and the importance of tailored nutritional approaches for diverse athletic endeavors. The evolving landscape of sports nutrition is also explored, with a specific focus on the benefits and potential risks associated with protein and creatine supplementation. Summary: In summary, this article serves as a comprehensive resource for athletes, coaches, and parents seeking to navigate the intricate intersection of nutrition and young athletes. By elucidating evidence-based strategies and addressing the potential drawbacks and risks associated with certain supplements, the article aims to empower stakeholders with the knowledge needed to make informed decisions regarding the nutritional well-being of young athletes. It underscores the importance of individualized approaches, recognizing the diversity of young athletes and advocating for adaptable nutritional strategies that contribute to both immediate performance gains and sustained health and athletic success.